IIjelmslev Planes and Topological Hjelmslev Planes - Lorimer, Joseph (My University, 1971)
In this thesis we examine a generalized notion of ordinary two dimensional affine and projective geometries The first six chapters deal very generally with coordinatization methods for these geometries and a direct construction of the analytic model for the affine case. The last two chapters are concerned with a discussion of these structures viewed as topological geometries.
Keywords: affine; topological geometries; projective geometries; analytic